Analisis pengaruh perputaran modal kerja, struktur modal, dan ukuran perusahaan terhadap profitabilitas - Ardo Muhamad Richard; Endang Masitoh; Riana Rachmawati Dewi (Owner : Riset dan Jurnal Akuntansi, 2022)
This study looks at how changes in working capital turnover, capital structure, and firm size can affect a profitability. This study covers period from 2016-   2020. The data used in this study annual report for property and real estate sector companies listed on the Indonesia Stock Exchange between 2016 and 2020 period. The population used in this study is all  these companies. In this study, we use multiple linear regression analysis to analyze quantitative data. Sampling method using is objective sampling method Based on the sampling method, there are 13 company in the property and real estate sector that meet the criteria. Financial statement documentation The method used in this study is the method of collecting and recording annual report. The study looked at 65 samples from the company's annual report for 2016-2020. This Study found the working capital turnover and capital structure had an effect on profitability, while company size had no effect. The model determination test showed that the independent variables affected on profitability. This shows that an increase in working capital turnover and capital structure can increase on profitability, and conversely a decrease in working capital turnover and capital structure will reduce on profitability, but this shows that company size does not affect on profitability. Increasing or decreasing company size does not affect profit.